How does person-centered maternity care relate to postpartum contraceptive counseling and use? Evidence from a longitudinal study of women delivering at health facilities in Ethiopia - Elizabeth K. Stierman; Celia Karp; Jiage Qian; Solomon Shiferaw; Assefa Seme; Mahari Yihdego; Saifuddin Ahmed; Andreea A. Creanga; Linnea A. Zimmerman (Elsevier, 2024)
Objectives: This study examines the relationship between integrated, person-centered maternity care (PCMC), the provision of postpartum family planning (PPFP) services, and postpartum contraceptive use among women delivering at health facilities in Ethiopia. Study design: We analyze 2019-2021 longitudinal data from a representative sample of pregnant and recently postpartum women in Ethiopia. This study examines baseline, 6-week, and 6-month survey data collected from women who delivered at a health facility. Results: Maternity patients who reported more person-centered care were more likely to be counseled on postpartum contraceptive methods before discharge. Overall, 27.5% of women delivering in a health facility received family planning counseling before discharge, ranging from 15.2% in the lowest PCMC quintile to 36.3% in the highest PCMC quintile. The receipt of PPFP counseling was associated with increased odds of postpartum contraceptive use. Conclusions: Findings suggest dimensions of quality care are interlinked, and person-centered care is associated with greater integration of recommended PPFP services into predischarge procedures. However, even among women who report relatively high levels of person-centered care, our results highlight that family planning is not routinely discussed prior to discharge from delivery, and very few women receive a contraceptive method or referral prior to discharge. Implications: While most postpartum women report they wish to limit or space future pregnancies, the uptake of modern contraceptive methods in the postpartum period is low. As women increasingly opt to deliver in health facilities, further integration of family planning services into predischarge procedures within maternity care can improve contraceptive access. Data statement: The data used in these analyses were collected as part of the PMA Ethiopia study. Data are publicly available at https://www.pmadata.org/data/request-access-datasets.